Specifying boundary conditions for the operation of pipe heating systems with impact on the building energy balance - Jakub Spurný; Michal Kabrhel (Acta Polytechnica CTU Proceedings, 2022)
Unaddressed boundary conditions in the design of heating systems affect the energy balance of buildings, especially in buildings with very low energy consumption. Buildings with very low energy consumption are very sensitive to any heat flow and neglecting realistic heating water parameters affects their energy balance. Two simulation models of the end part of the heating system have been developed. The first simulation model shows the effect of the inaccuracy of the designed heating element on the calculated room temperature. The second model shows the hydraulic behaviour of the connection pipes of the designed heating element.